Inflammation and blood-brain barrier breach remote from the primary injury following neurotrauma - Smith, N.; Giacci, M.; Gough, A.; Bailey, C.; McGonigle, T.; Black, A.; Clarke, T.; Bartlett, C.; Swaminathan Iyer, K.; Dunlop, S.; Fitzgerald, Melinda (BioMed Central, 2018)
Background: Following injury to the central nervous system, increased microglia, secretion of pro- and anti-inflammatory cytokines, and altered blood-brain barrier permeability, a hallmark of degeneration, are observed at and immediately adjacent to the injury site. However, few studies investigate how regions remote from the primary injury could also suffer from inflammation and secondary degeneration. Methods: Adult female Piebald-Viral-Glaxo (PVG) rats underwent partial transection of the right optic nerve, with normal, age-matched, unoperated animals as controls. Perfusion-fixed brains and right optic nerves were harvested for immunohistochemical assessment of inflammatory markers and blood-brain barrier integrity; fresh-frozen brains were used for multiplex cytokine analysis. Results: Immediately ventral to the optic nerve injury, immunointensity of both the pro-inflammatory biomarker inducible nitric oxide synthase (iNOS) and the anti-inflammatory biomarker arginase-1 (Arg1) increased at 7 days post-injury, with colocalization of iNOS and Arg1 immunoreactivity within individual cells. CD11b+ and CD45+ cells were increased 7 days post-injury, with altered BBB permeability still evident at this time. In the lower and middle optic tract and superior colliculus, IBA1+ resident microglia were first increased at 3 days; ED1+ and CD11b+ cells were first increased in the middle and upper tract and superior colliculus 7 days post-injury. Increased fibrinogen immunoreactivity indicative of altered BBB permeability was first observed in the contralateral upper tract at 3 days and middle tract at 7 days post-injury. Multiplex cytokine analysis of brain homogenates indicated significant increases in the pro-inflammatory cytokines, IL-2 and TNFa, and anti-inflammatory cytokine IL-10 1 day post-injury, decreasing to control levels at 3 days for TNFa and 7 days for IL-2. IL-10 was significantly elevated at 1 and 7 days post-injury with a dip at 3 days post-injury. Conclusions: Partial injury to the optic nerve induces a complex remote inflammatory response, characterized by rapidly increased pro- and anti-inflammatory cytokines in brain homogenates, increased numbers of IBA1+ cells throughout the visual pathways, and increased CD11b+ and ED1+ inflammatory cells, particularly towards the synaptic terminals. BBB permeability can increase prior to inflammatory cell infiltration, dependent on the brain region.